Análise da cobertura vacinal entre idosos indígenas no município de Carnaubeira da Penha: desafios e perspectivas (2012–2022) - Silva, Amanda Vitória da (Universidade Federal de São Carlos, 2024)
Indigenous peoples in Brazil face significant challenges, especially in relation to limited access to health services and cultural barriers. The epidemiological profile of these populations is complex, with infectious and parasitic diseases still being one of the main causes of morbidity and mortality. Vaccination against certain infectious diseases is an example of preventive intervention that has a crucial impact on reducing mortality. This study aims to evaluate the vaccination coverage of indigenous elderly people in the municipality of Carnaubeira da Penha, in Pernambuco, seeking to identify possible difficulties and the strategies used to guarantee comprehensive care for this population. To this end, searches were carried out in DATASUS, using data from the National Immunization Program Information System (SI-PNI), based on the vaccination booklet and existing vaccination policies.
Analysis of vaccination coverage among indigenous elderly people in the municipality of Carnaubeira da Penha: challenges and perspectives (2012–2022)
Keywords: Imunização; Cobertura vacinal; Saúde Indígena; Programa nacional de imunização; Immunization; Vaccination coverage; Indigenous health; National immunization program; CIENCIAS DA SAUDE